Znaczenie zasad wielkopolskiej spółdzielczości dla ruchu spółdzielczego i rozwoju drobnej gospodarki w PRL - Ochociński, Stefan (Wydział Prawa i Administracji UAM, 1972)
The role of co-operative credit associations in the field of organizing local circulation of money and small-scale credit as well as in the field of stimulating development of small-scale production follows from the position of peasantry and handicraft in the model of national economy. The state policy was changing in that sphere and that is the reason why some structural changes took place in the co-operative credit associations, which are presented in this article in three stages covering the years 1944 - 1949, 1950 - 1955, and 1956 - 1971. A new economic policy defined in the resolutions of the Central Comittee of the Polish United Workers' Party at the full sessions in 1970 and 1971 extends the participation of co-operative credit associations in providing finance for economic development considerably. In the article a skeleton program of mutual pecuniary aid as well as adjusted forms of organization and the technique of co-operative banking system are presented on the basis of the best experiences gained by the co-operative credit associations in the district of Poznań. By putting the experiences into practice the co-operative credit associations may be given a stimulus to a more effective employment of the population's resources and the co-operative resources to activize local communities in accord with the public interest while training them up to be thrifty united and disciplined.
The Importance of the Principles of the Co-operative Societies in the Districts of Poznań for the Co-operative Movement and Development of Small-scale Economy in Polish People's Republic